2017
DOI: 10.1080/07388551.2017.1333082
|View full text |Cite
|
Sign up to set email alerts
|

Artificial cultivation of true morels: current state, issues and perspectives

Abstract: Morels (Morchella, Ascomycota), which are some of the most highly prized edible and medicinal mushrooms, are of great economic and scientific value. Morel cultivation has been a research focus worldwide for more than 100 years, and the outdoor cultivation of morels has succeeded and expanded to a large scale in China in recent years. In this study, we review the progress in recent research regarding the life cycle and reproductive systems in the genus Morchella and the current state of outdoor cultivation. Scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 36 publications
1
94
0
5
Order By: Relevance
“…A), indicated that ENB still had a positive effect on fruiting in the late phase. Only by retaining the ENBs to contact with the mushroom bed for at least 75 days, can the dry weight of fruiting body yield reach the average level in agricultural production reported previously (Liu et al ., ). The compounds resulting from ENB decomposition are likely exported to the mushroom bed via mycelial networks, as well as free diffusion and running‐off.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A), indicated that ENB still had a positive effect on fruiting in the late phase. Only by retaining the ENBs to contact with the mushroom bed for at least 75 days, can the dry weight of fruiting body yield reach the average level in agricultural production reported previously (Liu et al ., ). The compounds resulting from ENB decomposition are likely exported to the mushroom bed via mycelial networks, as well as free diffusion and running‐off.…”
Section: Discussionmentioning
confidence: 97%
“…Ascocarps (fruiting bodies) were once produced in walk‐in growth chambers (Ower et al ., ), but further development of this method ceased, as repeating Ower's success by others has proven difficult (Masaphy, ). Although several kinds of morel cultivating techniques emerged in the last two decades (Liu et al ., ), morel cultivation industry was boosted only after the breeding of several black morel varieties with improved fruiting yield and stability (Peng et al ., ; Liu et al ., ), and more importantly, the development and widespread application of an appropriate organic substrate contained in the so‐called exogenous nutrient bag (ENB), a special type of culture substrate enriched in plant polysaccharides. Thanks to the ENB technique, cultivation of black morel expanded rapidly in China from 200 ha in 2011 to over 1200 ha in 2015 (Liu et al ., ), which generated the exportation of dried fruiting bodies from 180 to 900 tons between 2011 and 2015 (Du et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cultivated species of mushrooms belong to the phylum Basidiomycota , although some Ascomycota such as members from the genera Morchella or Tuber have also been successfully cultivated and commercially exploited (Rubini et al 2014 ; Liu et al 2017 ). Unlike plants, mushrooms are heterotrophic organisms which require external nutrients to grow; the vegetative mycelium (hypha network) supplies nutrients for the growth of basidiomes (reproductive stage) (Taylor and Ellison 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Morchella spp. have been documented to form mycorrhizae with trees (Dahlstrom et al 2000;Rossbach et al 2017) but they can also be saprotrophs (Liu et al 2017). It has also been shown that Morchella spp.…”
Section: Introductionmentioning
confidence: 99%